(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Neonatal cholestasis is a hepatobiliay disease characterized by biliary obstruction in the neonatal period. Biochemically it is evidenced by prolonged elevation of serum conjugated bilirubin beyond the first 14 days of life.1 Most common causes are biliary atresia and idiopathic neonatal hepatitis.3, 4 Objective: To evaluate stool color as a screening test by visual inspection in infants with prolonged neonatal cholestasis. Methodology: This was a cross-sectional analytic study, conducted in Pediatric Gastroenterology and Nutrition Department,BSMMU, Dhaka, from 3 September 2012 to 3 February 2013 about 6 month duration. Statistically calculated 38 infants with prolonged neonatal direct hyperbilirubinaemia beyond their 14 days of age were included in this study. Results: The mean age of the subjects was 62.3 days with a standard deviation (SD) ±13.7 days. Male to female ratio was 1.2:1. All (100%) the subjects were icteric and hepatomegaly was found in 94.7% subjects. Dark urine (84.2%), pale stool (78.5%), bleeding manifestations (31.8%) and infection (29%) were also observed. Thirty (78.5%) subjects had pale colored stool. Mean (± SD) albumin and conjugated bilirubin levels were 3.68 (±1.88)gm/dl and 5.29 (±1.31)mg/dl respectively. ALT and GGT level of the study subjects were 346.19±124.28 u/dl and 315±198.91 u/l respectively. Common ultrasonographic findings of the patients were non visualization of gallbladder 60.5%, non-visualization of common bileduct 50%, hepatomegaly 92.1%, and triangular cord sign in portahepatis 7.9%. Scintigraphy revealed impaired excretion into intestine 88.9% in majority of the subjects. Liver biopsy revealed liver architecture was preseved 65.8% bile duct proliferation 52.6%, regenarating nodule was absent 65.8% gaint cell was present 52.6% portal tract inflammation was found in 47.4%. Sensitivity of stool color in the diagnosis of neonatal cholestasis was found 90.6%, specificity 83.3%, accuracy 89.5%, positive predictive value 96.7% and negative predictive value 62.5%. Conclusion: It can be concluded that stool color might be reliable indicator for screening of prolonged neonatal cholestasis namely biliary atresia. J Bangladesh Coll Phys Surg 2021; 39(1): 46-52